KEBERHASILAN MINUM OBAT PUYER BAGI BALITA DENGAN MENGGUNAKAN GULA PASIR DI WILAYAH KERJA PUSKESMAS PASSO AMBON - Dene Fries Sumah (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2019)
Childrens do not like the bitter taste of drug and it becomes a barrier to drug administration. The more bitter of drug, the more likely the drug will be rejected. The sweet taste of drug can increase the ability of child patients to adhere to drug therapy. The study aims to determine the effect of giving sugar to the success of taking pulveres medicine to childrens in the Passo Health Center Working Area. The research method used is the true experiment with the post test only control group, is experimental design by comparing the post test data between the experiment groups and the control group. The samples in this study were 22 respondents, and were divided into control group and intervention group. The results were tested using the Mann Whitney statistical test. The results showed that there was effect for sugar to the success of taking pulveres medicine to childrens in the Passo Health Center Working Area. In the experiment group 11 respondents (50%) succeeded in taking pulveres medicine, in the control group 2 respondents (9,1%) succeeded in taking pulveres medicine, and based on Mann Whitney test p value = 0,000 < 0,05 meaning that there was an effect of giving sugar to the success of taking pulveres medication on childrens in the working area of the Passo Health Center. For health workers can educate how to overcome the problem of taking medication for childrens, by giving sugar ¼ teaspoon (1 gram) shortly after the drug is taken so as toddlers not to vomit because of the bitter taste of drug, and for the next researcher to be able to continue this research by observing other variables related to this study, for example age can influence the success of taking pulveres medicine in childrens, and using more samples. Keywords: the success of taking medication, sugar, childrens.